OPTIMALISASI PENEGAKAN SANKSI ADMINISTRASI PADA PELANGGAR PERATURAN WALIKOTA AMBON NOMOR 4 TAHUN 2020 TENTANG KAWASAN TANPA ROKOK DI KOTA AMBON - Asrul Pratama; Ali Maskur (Kampus Akademik Publiser, 2024)
The free use of cigarettes is very dangerous for public health and the environment, so the Government established the No Smoking Area (KTR) policy in Law Number 36 of 2009 concerning Health and Government Regulation Number 109 of 2012 concerning the Safety of Materials Containing Addictive Substances in the Form of Tobacco Products for Health. Administrative sanctions against violators of KTR have been regulated in Ambon City Regional Regulation No. 4 of 2020 concerning KTR and Ambon City Regulation No. 15 of 2022 concerning Implementation Guidelines for Regional Regulation No. 4 of 2020 concerning KTR. However, the enforcement of these administrative sanctions has not been implemented. The research method used in writing this scientific work is to use an empirical juridical method which is descriptive in nature, namely linking the application of legal rules or regulations in this problem with facts and data in the field. The results of writing this scientific work show the main factors of the problem in optimizing the enforcement of administrative sanctions on violators of the regulation of the Mayor of Ambon City No. 4 of 2020 concerning KTR, among others: first is the legal factor where the content of legal norms related to the scope of validity of the KTR Regional Regulation exceeds the boundaries of the authority of the Ambon City Government itself such as taking care of and supervising the Hospital area which is under the auspices of the Provincial Health Office; second is the law enforcement factor where the KTR Task Force has not been formed; and third is the KTR facilities and facilities factor where the lack of budget allocation for the implementation of this policy. So that the enforcement of administrative sanctions cannot be applied.